AHP Based Evaluation Model of Energy Efficiency for Energy Internet - Wang Qing; Liu Song; Li Congcong; Yu Chao; Liu Yanxi (E3S Web of Conferences, 2021)
The emerging construction of China’s industry park requires for a specific evaluation method for the local energy internet’s power utilization efficiency. This article focuses on the solar power exploitation from power supply reliability, energy utilization efficiency, solar power general efficiency, established a complete energy internet evaluation index system using improved analytic hierarchy process (AHP). Such method was proved to be more delicate to evaluate the solar-involved park energy internet comparing to traditional methods. The energy internet of a certain industry park was taken as an example for verification. It was found that the improved AHP method can objectively reflect the planning’s efficiency from multi-indicators. When evaluating from different perspective, focusing on a different characteristic of the regional power grid will lead to changes in the AHP evaluation weighting and the results. According to the evaluation result, the relevant suggestions to improve energy efficiency were also proposed.